2012
DOI: 10.1093/aje/kws141
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Serum 25-Hydroxyvitamin D and Vitamin D-Binding Protein Levels Over Time in a Prospective Cohort Study of Black and White Adults

Abstract: Prospective epidemiologic studies generally rely on 1 baseline biologic sample from participants for measurement of prediagnostic biomarkers, assuming that 1 measurement adequately represents the participant's "typical" level. The body of work assessing the reproducibility of circulating serum 25-hydroxyvitamin D (25(OH)D) levels over time focuses almost exclusively on populations of European descent, and data for vitamin D-binding protein (VDBP) are virtually nonexistent. Thus, the authors measured levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 30 publications
0
64
0
Order By: Relevance
“…Although high intra-individual reproducibility of serum 25(OH)D levels over time has been reported [35], the use of single serum 25(OH)D levels is one limitation of our study. Regarding smoking status, although a direct measure can be obtained by measuring cotinine levels in biological fluids, most population studies, including the HUNT Study, rely on self-report.…”
Section: Discussionmentioning
confidence: 91%
“…Although high intra-individual reproducibility of serum 25(OH)D levels over time has been reported [35], the use of single serum 25(OH)D levels is one limitation of our study. Regarding smoking status, although a direct measure can be obtained by measuring cotinine levels in biological fluids, most population studies, including the HUNT Study, rely on self-report.…”
Section: Discussionmentioning
confidence: 91%
“…However, results from a recent prospective study in the US suggested high intra-individual reproducibility over time [30]. We excluded 15% of asthma cases due to missing data on exposure and/or outcomes which may lead to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in preschool children in the UK, mean 25(OH)D was approximately 70% higher in summer compared to winter [16], yet the potential tracking of 25(OH)D throughout the year has not been elucidated. Reproducibility of 25(OH)D status in samples obtained in the same month at one to 5 year intervals has been demonstrated in adults [104,105]. However, stability in the rank of an individual's 25(OH)D measurement within the population distribution at several time points during childhood/adolescence or across seasons is unknown.…”
Section: Vitamin D Status and Bmd In Childhood And Adolescencementioning
confidence: 99%